2000
DOI: 10.1128/iai.68.7.4225-4237.2000
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcus neoformansIs a Facultative Intracellular Pathogen in Murine Pulmonary Infection

Abstract: To produce chronic infection, microbial pathogens must escape host immune defenses. Infection with the human pathogenic fungus Cryptococcus neoformans is typically chronic. To understand the mechanism by which C. neoformans survives in tissue after the infection of immunocompetent hosts, we systematically studied the course of pulmonary infection in mice by electron microscopy. The macrophage was the primary phagocytic cell at all times of infection, but neutrophils also ingested yeast.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
421
1
5

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 411 publications
(451 citation statements)
references
References 56 publications
24
421
1
5
Order By: Relevance
“…Isc1 REGULATES NEUROTROPISM OF CRYPTOCOCCUS NEOFORMANS 5985 phagolysosomes (13,44). Our studies show that Isc1 is important for C. neoformans to survive intracellularly.…”
Section: Vol 74 2006mentioning
confidence: 73%
See 1 more Smart Citation
“…Isc1 REGULATES NEUROTROPISM OF CRYPTOCOCCUS NEOFORMANS 5985 phagolysosomes (13,44). Our studies show that Isc1 is important for C. neoformans to survive intracellularly.…”
Section: Vol 74 2006mentioning
confidence: 73%
“…J774.16 is a murine reticulum sarcoma macrophage-like cell line that is well characterized (7) and is extensively used as a model for cryptococcal interactions with macrophages (13,44). J774.16 cells were used up to passage 10, with each passage dilution equal to 1:12.…”
Section: Fig 2 Deletion and Reconstitution Of Isc1 In C Neoformansmentioning
confidence: 99%
“…During infection, cryptococcal polysaccharide accumulates in tissues (14). Released polysaccharide is a potent immunomodulator (37) and toxic to phagocytic cells (10). Previous studies have shown that subinhibitory concentrations of amphotericin B and fluconazole increase capsular release (27).…”
Section: Discussionmentioning
confidence: 99%
“…The main component of the capsule is glucuronoxylomannan (GXM), 3 which is antiphagocytic in vitro and has been demonstrated to cause a variety of deleterious effects to immune function (1). Despite its antiphagocytic properties in vitro, C. neoformans is a facultative intracellular pathogen in vivo (3). Although it is a relatively rare cause disease in normal individuals, C. neoformans is a relatively frequent cause of chronic meningitis in patients with impaired immune function (reviewed in Ref.…”
Section: Ryptococcus Neoformans Is the Only Pathogenic Fungusmentioning
confidence: 99%